Internalisasi Multikulturalisme dalam Berbangsa pada Lembaga Pendidikan Pondok Pesantren (Studi pada Pondok Pesantren se-Kota Metro) - J Sutarjo (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2018)
Conflicts related to multicultural are widely reported in mass media and electronics in various forms such as demonstrations and other blasphemies related to differences in Indonesia. This shows that many people still do not understand multiculturalism. If it is realized that it does not need to happen because the diversity that exists should be understood because in essentially multicultural have a purpose to understand each other and compete in goodness with ” taqwa” to Allah SWT. In multicultural studies multiculturalism is seen as Politic of Recognition; building awareness of cultural diversity, traditions or preserved habits. Recognition and acceptance of the condition is a politic of recognition that must be upheld. This includes; 1) Multicultural in Etnic and Cultural Groups. 2) Society in Metaphors of Mixed Culture. 3) Multiculturalism in Social Characteristics. 4) Hyperculturalism as a new view. From the study conducted in “pesantren cottage” in Metro city, multicultural multiculturalization has been done although has not been integrated into the curriculum of boarding school education officially.